The Use of The Lucidspark Application in Learning Argumentative Text in Senior High School - Kautsari, Diva Akmalita; Huda, Miftakhul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe how the Lucidspark application is applied in learning argumentative texts at the high school level, focusing on its role as an interactive medium to support writing, collaboration, and critical discussion. Methodology: Using a qualitative design, data were gathered from students, teachers, and the learning process through observations, questionnaires, interviews, and review of relevant literature. The raw data—comprising words, sentences, and written paragraphs detailing the Lucidspark implementation steps—were processed through a five‐stage analysis: preparing data, full data reading, data coding, theme development, and results presentation. Data validity was ensured via triangulation across multiple sources and methods. Results: Implementation of Lucidspark in argumentative‐text lessons unfolded in clear preparation and execution phases. Teachers and students reported that Lucidspark effectively facilitated group discussions and mind‐mapping activities. However, unstable internet connectivity and occasional student rule violations posed challenges. Quantitatively, 93.1% of students achieved scores above the minimum competency standard, while 6.9% did not. Regarding user satisfaction, 21% of students were very satisfied, 45% satisfied, and 34% fairly satisfied with Lucidspark’s integration into their learning. Applications/Originality/Value: By demonstrating Lucidspark’s capacity to foster interactive, technology‐based learning, this study offers a practical model for integrating digital collaboration tools into language curricula. It highlights how real‐time mapping and discussion features can enhance argumentative writing skills, providing educators with actionable insights for adopting similar ed‑tech solutions to enrich student engagement and learning outcomes.